Lack of association of glutathione S-transferase gene polymorphisms in Iranian prostate cancer subjects - Basir, Sahar Ansari; Vasudevan, Ramachandran; Mirinargesi, Mirsaed; Ismail, Patimah; Abdul Rahman, Sabariah; Pasalar, Parvin; Bakhshi, Ali (Science Publications, 2009)
Problem statement: Glutathione S-transferase is super family genes that encode enzymes which involve in the detoxification of the cell and protects DNA from damage. Conflicting results was found in several studies in association with GSTT1 and GSTM1 gene polymorphisms and prostate cancer. In this study, we determined the association between the GSTT1 and GSTM1 gene polymorphism and prostate cancer in Iranian subjects as control with control subjects.